Kepentingan Turki dalam Melakukan Impor Sampah Plastik dari Eropa Periode 2019 – 2021 - Agus Nilmada Azmi; Amirah Syahirah (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2023)
This study analyzes Turkey's interest in importing plastic waste from European countries in the period 2019–2021. The import of plastic waste has become an alternative waste management method that is considered more efficient, can reduce the load on local landfills, and meets certain standards in environmental management. The study used a descriptive-qualitative approach. The study concludes that global plastic waste management faces serious challenges due to the lack of adequate plastic waste management infrastructure. Its causes developed countries such as Europe to export their plastic waste to developing countries, including Turkey. The main factors influencing Turkey's plastic waste import policy are of economic and strategic importance. Turkey imports plastic waste as a raw material that can reduce production costs and gain economic benefits in a circular economy model. However, Turkey's plastic waste import policy also has a negative impact on the environment and health. Turkey needs to pay attention to the environmental and health impacts of plastic waste import activities and develop more sustainable plastic waste management strategies at the national level.